2021
DOI: 10.3389/fendo.2021.705264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cumulative Live Birth Rates of Progestin-Primed Ovarian Stimulation and Flexible GnRH Antagonist Protocols in Patients With Low Prognosis

Abstract: ObjectiveTo compare the cumulative live birth rate (CLBR) of the progestin-primed ovarian stimulation (PPOS) protocol with that of the flexible GnRH antagonist protocol in patients with poor prognosis diagnosed per the POSEIDON criteria.MethodsThis was a retrospective cohort study. Low-prognosis women who underwent IVF/ICSI at the Reproductive Center of Third Affiliated Hospital of Zhengzhou University between January 2016 and January 2019 were included according to the POSEIDON criteria. The CLBR was the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 34 publications
(60 reference statements)
2
29
0
1
Order By: Relevance
“…Meanwhile, no statistically signi cant differences were found in Gn dosage, duration of ovarian stimulation, number of oocytes retrieved, number of 2PN embryos and CLBR between the PPOS and GnRH-Ant groups [13]. In accord with the previous research [17], the high cancellation rates were found in patients treated with the PPOS and GnRH-Ant regimens, especially patients in PPOS regimen.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Meanwhile, no statistically signi cant differences were found in Gn dosage, duration of ovarian stimulation, number of oocytes retrieved, number of 2PN embryos and CLBR between the PPOS and GnRH-Ant groups [13]. In accord with the previous research [17], the high cancellation rates were found in patients treated with the PPOS and GnRH-Ant regimens, especially patients in PPOS regimen.…”
Section: Discussionsupporting
confidence: 81%
“…For POSEIDON Group Another study for patients of POSEIDON Group 3 have found that GnRH-Ant group had higher LH levels on trigger day (5.1 ± 4.7 mIU/ml vs. 3.5 ± 2.4 mIU/ml, P = 0.08) and less available embryos (0.9 ± 0.8 vs. 1.2 ± 1.1, P = 0.07) than PPOS group, but without signi cant difference [13].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…By competing with endogenous GnRH for pituitary cell GnRH receptors, GnRH antagonists regulate pituitary surface GnRH receptor levels, inhibit early LH peaks and endogenous FSH and LH levels, more closely resemble the development of follicles under normal physiological conditions, prevent early follicular luteinization or ovulation, and result in more highquality eggs (12). PPOS (13) The European Society of Human (15) for patients with a low prognosis diagnosed according to the POSEIDON criteria, the CLBR of the PPOS regimen was comparable to that of the GnRH antagonist regimen. In contrast with the PPOS regimen, which supports fresh embryo transfer, the PPOS regimen must be combined with total freezing and delayed embryo transfer; therefore, the antagonist regimen significantly reduces the time to clinical pregnancy, consistent with the data from this trial, and the reduction in TTP may reduce patient anxiety to some extent (16).…”
Section: Discussionmentioning
confidence: 99%